2018
DOI: 10.1111/conl.12564
|View full text |Cite
|
Sign up to set email alerts
|

The major barriers to evidence‐informed conservation policy and possible solutions

Abstract: Conservation policy decisions can suffer from a lack of evidence, hindering effective decision-making. In nature conservation, studies investigating why policy is often not evidence-informed have tended to focus on Western democracies, with relatively small samples. To understand global variation and challenges better, we established a global survey aimed at identifying top barriers and solutions to the use of conservation science in policy. This obtained the views of 758 people in policy, practice, and resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 40 publications
2
103
1
Order By: Relevance
“…This collaborative exercise may include the co-design of research questions and search for adequate funding sources that depend on stakeholder priorities. In this way the observed disagreement between priorities of research scientists and other stakeholders, previously identified in other contexts (Arlettaz et al, 2010;Rose et al, 2018) can be avoided, and societal needs taken into account. Using value of information approaches (Nicol, Ward, Stratford, Joehnk, & Chadès, 2018;Runge, Converse, & Lyons, 2011) might be used to help deciding on priorities, particularly to disentangle the relative importance of social values given by stakeholders to different topics and the real lack of scientific knowledge on those topics.…”
Section: Resultsmentioning
confidence: 91%
“…This collaborative exercise may include the co-design of research questions and search for adequate funding sources that depend on stakeholder priorities. In this way the observed disagreement between priorities of research scientists and other stakeholders, previously identified in other contexts (Arlettaz et al, 2010;Rose et al, 2018) can be avoided, and societal needs taken into account. Using value of information approaches (Nicol, Ward, Stratford, Joehnk, & Chadès, 2018;Runge, Converse, & Lyons, 2011) might be used to help deciding on priorities, particularly to disentangle the relative importance of social values given by stakeholders to different topics and the real lack of scientific knowledge on those topics.…”
Section: Resultsmentioning
confidence: 91%
“…Limited resources and time frames, and a lack of access to pertinent information, however, mean that the ecological knowledge used in management is often less than ideal (Pullin et al 2003). Under these constraints, there is a need to improve mechanisms to ensure that the best available science is relevant and accessible to policy and management (Rose et al 2018). Fundamental to this is the establishment of relationships between researchers and managers that foster the acquisition and dissemination of science (Safford et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Rose et al. ). Publication incentives are one of the most important science policies, but they can restrict scientists from producing useful science (Neff ) and from participating in collaborations (Shanley & López ).…”
Section: Discussionmentioning
confidence: 98%